Pelatihan Desain Site Plan Reservoir untuk Menampung Sumber Mata Air di Wisata Bukit Tangkeban Kabupaten Pemalang - Hendra Hermawan , Okky; Luthfianto, Saufik (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
The site plan design with a water reservoir (reservoir) will be used to design water needs in Nyalembeng village, Pemalang regency. The stages before the reservoir site plan training are knowing the water discharge in the banding river spring, measuring the length of the river width, knowing whether or not the place is suitable for the reservoir to be built, and surveying the distance from the banding river to Tangkeban hill, mapping surveys for clean water installation lines and electrical installations. The results achieved in this training were 57% getting the excellent category and 33% in the good category in designing the reservoir site plan